I'jaz Al- Quran al- Lughawi - Fathurrahman Rauf (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
Al-Qur'an is Allah's verses revealed to the universe and as a miracle of Rasulullah (pbuh) arranged in good and beautifulArabic, in which Arabs and their poets at that time could not equal and make it well even little. The miracle of Qur'an well knownin its language and literature which includes all aspects like in phisical structure (language style) and inner structure (its contentand message)